Pelayanan Publik Inklusif di Era Digital: Studi Aksesibilitas Website Pemerintah Daerah bagi Penyandang Disabilitas - Aditya Sulthony Ahmad Khan; Tri Cahyo Nugroho Nugroho; Ayunytyah Eka Wardani; Muhammad Novrizal Ramadhan (PT. Palem Edukasi Nusantara, 2025)
The rapid expansion of digital transformation in the public sector has been widely promoted as a means to enhance efficiency, transparency, and service quality. However, these advances often fail to accommodate the needs of persons with disabilities, thereby reinforcing existing inequalities in accessing public services. This study explores how inclusive digital governance can be achieved by focusing on the accessibility of digital public services for people with disabilities in Bengkulu Province, Indonesia. Employing a qualitative descriptive approach, data were gathered through document analysis, field observations, and the assessment of selected government websites using the Web Content Accessibility Guidelines (WCAG) framework. The findings reveal that although Bengkulu Province has developed more than one hundred digital platforms, many lack basic accessibility features—such as screen reader compatibility, keyboard navigation, and visual contrast adjustments—making them difficult to use for individuals with visual, motor, or cognitive impairments. Conversely, certain institutions demonstrate best practices by integrating accessible design that supports assistive technologies. These results highlight the pressing need for local governments to adopt universal design principles, strengthen technical standards, and improve institutional capacity to comply with the rights guaranteed under the Disability Act and related regional regulations. The study concludes that inclusive public service delivery in the digital era requires not only technological adaptation but also policy commitment and cross-sectoral collaboration to ensure equitable participation of all citizens.